PWE-034 Diagnostic Yield and Safety of 'Bite on Bite' Tunneled Biopsy for Sampling of Upper Gastro-Intestinal Submucosal Lesions. (4th June 2013) - Evans, J A; Halketson, K; Ismail, D; Leahy, A; Fullard, M; Finerty, E; Richman, P
Abstract : Introduction: Submucosal lesions are detected incidentally in a small proportion of diagnostic upper gastro-intestinal endoscopies. Endoscopic ultrasound guided fine needle aspiration (EUS-FNA) and endoscopic submucosal resection (ESMR) are useful diagnostic investigations for the assessment of such submucosal lesions with studies reporting diagnostic yields of 42% - 92% and 87% respectively. 1, 2, 3 However, access to these techniques is usually limited to specialist centres and they can have complications, with bleeding rates for ESMR ranging from 0–24% 3 . The diagnostic yield with standard sized biopsy forceps is recognised as very low when assessing submucosal lesions. 3 However, there is some evidence that this diagnostic yield might be increased to 17–38% by using a repeated "bite on bite" technique with larger capacity forceps. 3 Methods: We evaluated the diagnostic yield and safety of "bite on bite" tunnelled biopsy in diagnosing submucosal lesions found on upper gastro-intestinal endoscopy. Data from 30 patients who underwent tunnelled biopsy was prospectively collected over an 18 month period. The acquisition of tissue required repeated biopsies consisting of 6 bites from the same point using a biopsy forceps with an open jaw diameter of 7mm (Radial jaw 4 large capacity, Boston Scientific). Results: 30 patients were included; (18 male, median age 60 years: range 31–79). The diagnostic yield on tunnelled biopsy was 7/30 (23.33%). Positive sample sites were: 4/12 oesophageal (1 mycobacterium tuberculosis, 3 leiomyomas), 0/13 gastric, 3/5 duodenal (1 pancreatic tissue, 2 endocrine carcinomas). No sampling led to bleeding requiring additional therapy to gain haemostasis. No patient required readmission with complications related to tunnelled biopsy within 30 days of their procedure. Conclusion: The tunnelled 'bite on bite' biopsy technique produced a low positive diagnostic yield of 23.33% when compared to EUS-FNA and ESMR. However, there were no complications with this method. Despite its low yield, tunnelled biopsy could still be considered as an initial diagnostic method for investigating incidental submucosal lesions as it is inexpensive to perform, safe and universally available. Disclosure of Interest: None Declared. References: Hunt G, Smith P, Faigel D. Yield of tissue sampling for submucosal lesions evaluated by EUS. Gast. Int. Endosc 2003; 57(1):68–72. Jessen C, Dietrich C Endoscopic ultrasound –guided fine needle aspiration biopsy and trucut biopsy in gastroenterology – An overview. Best Practice & Research, Clin Gast. 2009: 25(5):743–59. Cantor M, Davila R, Faigel D. Yield of tissue sampling for submucosal lesions evaluated by EUS: comparison between forceps biopsies and endoscopic mucosal resection. Gast. Int. Endosc. 2006:64(1): 29–34.